Brazilian primary school teachers' knowledge about immediate management of dental trauma - Matheus Melo Pithon; Rogério Lacerda dos Santos; Pedro Henrique Bomfim Magalhães; Raildo da Silva Coqueiro (Dental Press Editora, 2014)
OBJECTIVE: To assess the level of knowledge of primary school teachers in the public school network of Northeastern Brazil with respect to management of dental trauma and its relationship with prognosis. METHODS: A questionnaire was applied to 195 school teachers of public schools in Northeastern Brazil. The questionnaire comprised 12 objective questions about dental trauma and methods for its prevention and management. Data were submitted to chi-square test and Poisson regression test (P > 0.05). RESULTS: Out of the 141 teachers who responded the questionnaires, the majority were women (70.2%) and most of them had experienced previous dental accidents involving a child (53.2%). The majority (84.4%) had incomplete college education and few were given some training on how to deal with emergency situations during their undergraduate course (13.5%) or after it (38.3%). Their level of knowledge about dental trauma and emergency protocols showed that unsatisfactory knowledge level was associated with the male sex: 46% higher for men in comparison to women (P = 0.025). CONCLUSIONS: Approximately half of teachers evaluated had unsatisfactory knowledge about dental trauma and emergency protocols, with female teachers showing more knowledge than men.